Osh Problems and Improvıng Suggestıons ın Metal Sector of Turkey Wıthın the Perspectıve of Employees - Ozkan, Yilmaz; Arpat, Bulent (European Scientific Journal, ESJ, 2017)
Metal sector in Turkey is the sector that has the highest workaccident rate. The aim of the paper is to acquire feedback in two issues from employees in metal sector so that improvements required for high priority fields could be detected and work-accident rate could be reduced to a certain level as well. While the first issue, consists of factors which employees thought for that negatively affects Occupational Health and Safety (OHS) in the workplace environment, the second issue is their suggestions for changes in the improvements of OHS in the workplace. the research is conducted with 325 employees and 27 workplaces. In the first group, 427 views are taken out of 321 employees and in the second group 94 employees gave 97 answers. In this research, “content analysis” is used as the assessment method. According to results, factors that negatively affect OHS in Metal Sector are gathered in 13 basic group and suggestions for improvements are gathered in 8 basic groups.